The impact of administrative management and information technology on e-government success: The mediating role of knowledge management practices - Abdullah Fahad AlMulhim (Cogent Business & Management, 2023)
This study examines the impact of administrative management and information technology on e-government success with the mediation role of knowledge management practices. For this purpose, data was gathered from 163 public sector participants in the Al-Jouf region of Saudi Arabia. This study uses partial least squares structural equation modeling (PLS-SEM) to test and validate the research model and proposed hypotheses. The findings show that information technology and administrative management significantly increase e-government success and knowledge management practices. Moreover, the findings revealed that knowledge management practices play a vital mediating role between information technology and administrative management to make e-government success more successful and to reduce risk. Furthermore, this study strengthens the theoretical and practical implications of e-government by developing a link with socio-technical systems theory as well as with Fayol's administrative management theory. In the end, the study recommends that policymakers and managers take serious steps to attain advantages in the application of technologies in e-government to fulfill the renewable and changing needs of beneficiaries.
Keywords: 650; administrative management; Al-Jouf region; e-government success; information technology; knowledge management practices; Saudi Arabia